2014
DOI: 10.1097/sla.0b013e3182a6f45e
|View full text |Cite
|
Sign up to set email alerts
|

The HARM Score

Abstract: The HARM score is easy, reliable, and valid for assessing quality in colorectal surgery. It may provide a low-cost solution for comparative quality assessment in surgery focused on true outlier performance rather than process or clinical outcome metrics alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Considering that both length of stay and readmission rate were lower in the robotic group, it is reasonable to suggest that this may be due to reduced surgical morbidity. This is supported by two recent studies published by the Cleveland clinic group who reported that length of stay, readmission rate and mortality effectively predict complications [ 52 , 53 ]. Considering that mortality was equal between the two groups in our study, these studies strengthen our argument that the reduced readmission rate and length of stay in the robotic cohort are due to a lower surgical morbidity profile.…”
Section: Discussionsupporting
confidence: 54%
“…Considering that both length of stay and readmission rate were lower in the robotic group, it is reasonable to suggest that this may be due to reduced surgical morbidity. This is supported by two recent studies published by the Cleveland clinic group who reported that length of stay, readmission rate and mortality effectively predict complications [ 52 , 53 ]. Considering that mortality was equal between the two groups in our study, these studies strengthen our argument that the reduced readmission rate and length of stay in the robotic cohort are due to a lower surgical morbidity profile.…”
Section: Discussionsupporting
confidence: 54%
“…The scores differ from other performance measures used to describe outcomes and quality of surgery and can be calculated using available administrative data, without the additional cost of software or ongoing costs for maintenance or personnel. As there is no investment cost, Keller et al [ 5 ] reported that the HARM score may decrease administrative costs associated with quality care improvement programs. Hence, the BAR-HARM score may be a good alternative to expensive programs like the MBSAQIP, which are used to measure outcomes in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The categorical variables “discharge status” and “readmission” were defined as deceased/alive and yes/no, respectively. If the patient was deceased, the “readmission” variable was taken out of the equation, in accordance with the method described by Keller et al [ 5 ]. LOS was defined as the number of days from the date of initial bariatric or metabolic surgery to the date of hospital discharge and was categorized into the six categories as described in a previous study [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations